The Effects of Regulatory Scrutiny on Tax Avoidance: An Examination of SEC Comment Letters - Kubick, Thomas R.; Lynch, Daniel P.; Mayberry, Michael A.; Omer, Thomas C. (The Accounting Review, 2016)
ABSTRACT This study examines the tax avoidance behavior of firms prior to the issuance, and following the resolution, of SEC tax comment letters. We find that firms that appear to engage in greater tax avoidance are more likely to receive a tax-related SEC comment letter. We also find that firms receiving a tax-related SEC comment letter, relative to firms receiving a non-tax comment letter, subsequently decrease their tax avoidance behavior consistent with an increase in expected tax costs. Additionally, we document evidence consistent with other firms that do not receive a comment letter reacting to multiple publicly disclosed tax-related comment letters within their industry by increasing their reported GAAP ETR, consistent with an indirect effect of regulatory scrutiny on certain types of tax avoidance.